Analisis Faktor-Faktor Yang Mempengaruhi Nilai Informasi Pelaporan Keuangan Daerah - Titian Nurmaulidia; Muhammad Agus Salim; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Affect the value of regional financial reporting information. Indicator variable Value of Financial Report Information, Quality of Human Resources, Information Technology, Regional financial supervision, internal control system. The data used is primary data, which is obtained by distributing questionnaires by respondents, namely the chief of staff of the accounting/financial administration sub-section. Sampling was done using purposive sampling method. The sample of this study is the criteria for respondents in this study are employees who carry out accounting/financial administration functions at SKPD, which include the head and staff of the regional accounting/financial administration sub-section in Bima Regency. Data analysis used classical assumption test and multiple linear regression. The results of this study indicate that the variable Quality of Human Resources has a positive and significant effect on the Value of Information on Financial Statements in the Bima Regency, Utilization of Information Technology has a positive and significant effect on the Information Value of the Financial Reports in the Bima Regency, Regional Financial Supervision has a positive and significant effect on the Value of Report Information. The regional finance of the bima district, the Inter Control System has a positive and significant effect on the Information Value of the regional financial report of the bima district. Keywords: Value of Financial Report Information, Quality of Human Resources, Information Technology, Regional Financial Supervision, Internal Control System